2006
DOI: 10.1080/13552600601090329
|View full text |Cite
|
Sign up to set email alerts
|

Profiling stranger rapists: Linking offence behaviour to previous criminal histories using a regression model

Abstract: International research has suggested that rapist criminal histories can be predicted from certain offence behaviours. Ninety-six solved stranger rape cases were examined to determine if there was consistency in a New Zealand sample. Rapist behaviours during the offence were compared with criminal convictions prior to the rape. The primary statistical technique used was likelihood ratio stepwise binary logistic regression. Predictive utility of the results was limited, due to significant correlation coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…A coding dictionary was then created, on the basis of a number of previous studies on serial rape and sexual assault (Alison & Stein, ; Bootsma & Van Den Eshof, ; Canter et al , ; Dale, Davies, & Wei, ; Davies, ; Hazelwood & Warren, ; Goodwill & Alison, ; Grubin et al , ; Lundrigan et al , ; Park, Schlesinger, Pinizzotto, & Davis, ; Santtila et al , ; Scott, Lambie, Henwood, & Lamb, ; Woodhams et al , ). Initially, the coding dictionary comprised 150 dichotomous offender behaviours and offence characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…A coding dictionary was then created, on the basis of a number of previous studies on serial rape and sexual assault (Alison & Stein, ; Bootsma & Van Den Eshof, ; Canter et al , ; Dale, Davies, & Wei, ; Davies, ; Hazelwood & Warren, ; Goodwill & Alison, ; Grubin et al , ; Lundrigan et al , ; Park, Schlesinger, Pinizzotto, & Davis, ; Santtila et al , ; Scott, Lambie, Henwood, & Lamb, ; Woodhams et al , ). Initially, the coding dictionary comprised 150 dichotomous offender behaviours and offence characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Other attempts at linking offense characteristics to sex offender characteristics have used either some forms of multidimensional scaling (Canter et al, 2003;Häkkänen, Lindlöf, & Santtila, 2004;Kocsis, Cooksey, & Irwin, 2002) or regression analyses (e.g. Beauregard, Lussier, & Proulx, 2007a;Goodwill & Alison, 2007;Scott et al, 2006). In this issue, ter Beek, van den Eshof, and Mali used logistic regression on a sample of 271 stranger rape offenses included in the ViCLAS database of The Netherlands, and found that crime characteristics can be used to 'profi le' offender characteristics, thus providing further weight to the A → C equations.…”
Section: The a → C Equationsmentioning
confidence: 99%
“…Criminal career has proven very promising in the prioritisation of suspects (Scott, Lambie, Henwood, & Lamb, 2006). Police offi cers often rely on information about known suspects or offenders who were previously charged and convicted for a similar offense in order to start their investigation.…”
Section: Recidivism Patterns Of Different Types Of Sex Offendersmentioning
confidence: 99%
“…Some authors have favoured direct bivariate associations to explore the relationship between single offence behaviors and prior offences (e.g. Almond et al, 2018;Cole & Brown, 2014;Davies et al, 1997;Lea, Hunt, & Shaw, 2011;Scott, Lambie, Henwood, & Lamb, 2006;ter Beek, van den Eshof, & Mali, 2010). In the context of stranger rape, for example, Almond et al (2018) found in their replication of the classic Davies et al…”
Section: Introductionmentioning
confidence: 99%